Rekonfigurasi Antena Folded Dipole Mikrostrip Berbasis Laser Merah dan Microwave Multifunctional Analyzer (MMA) - Aslam Chitami Priawan Siregar; Yono Hadi Pramono; Gatut Yudoyono; Ni’matut Tamimah (Universitas Nurul Huda, 2025)
With the increasing use of communication devices across various regions, antennas with stable signal performance are essential to ensure reliable information transmission. In this study, a microstrip folded-dipole antenna operating in the SHF band was developed using a reconfiguration mechanism based on a 650-nm red laser and metamaterial absorber (MMA). The initial antenna structure was designed and simulated in CST software with a target operating frequency of 9 GHz. Experimental results show that the antenna without a resonator exhibits an operating frequency of 13.77 GHz when the laser is off and 3.15 GHz when the laser is on. When integrated with the resonator, the operating frequencies shift closer to the simulation results, ranging from 15.75 GHz (laser off) to 7.02 GHz (laser on). The return-loss performance also improves with the implementation of the resonator. Without the resonator, the antenna achieves −33 dB return loss in laser-off mode and −34.15 dB in laser-on mode. With the resonator, the return loss values are −21.88 dB (laser off) and −26.61 dB (laser on). These findings indicate that the proposed configuration technique is applicable for outdoor Wi-Fi signal enhancement in the 5 GHz band and as a blind-spot sensing element for automotive radar systems.